2008
DOI: 10.1111/j.1538-7836.2008.03016.x
|View full text |Cite
|
Sign up to set email alerts
|

Compromised ITAM‐based platelet receptor function in a patient with immune thrombocytopenic purpura

Abstract: Summary. Background: Receptors on platelets that contain immunoreceptor tyrosine-based activation motifs (ITAMs) include collagen receptor glycoprotein (GP) VI, and FccRIIa, a low affinity receptor for immunoglobulin (Ig) G. Objectives: We examined the function of GPVI and FccRIIa in a patient diagnosed with immune thrombocytopenic purpura (ITP) who had unexplained pathological bruising despite normalization of the platelet count with treatment. Methods and Results: Patient platelets aggregated normally in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 43 publications
2
58
1
Order By: Relevance
“…Plasma sGPVI is only derived from platelets and could provide a new readout for metalloproteinase activity in the context of coagulation, although plasma sGPVI may become elevated because of other causes, such as acute coronary syndrome, acute ischemic stroke, or autoimmune disease. 35,42,55 Large-scale prospective studies would be required to evaluate sGPVI in the context of coagulation defects or anticoagulant treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma sGPVI is only derived from platelets and could provide a new readout for metalloproteinase activity in the context of coagulation, although plasma sGPVI may become elevated because of other causes, such as acute coronary syndrome, acute ischemic stroke, or autoimmune disease. 35,42,55 Large-scale prospective studies would be required to evaluate sGPVI in the context of coagulation defects or anticoagulant treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were immunoblotted with anti-GPVI cytoplasmic tail IgG as described. 21,23,35 To assess a requirement for intracellular signaling, washed platelets were treated for 1 hour with FXa and 10M Src inhibitor PP2, 20M BAPTA-AM, 1 g/mL rivaroxaban, or 10M PAR1 inhibitor SCH79797. Platelets treated with 10M phorbol myristate acetate were included as a positive control.…”
mentioning
confidence: 99%
“…Polyclonal rabbit anti-human GPVI antibody was raised against recombinant human GPVI extracellular domain (residues 21-234, excluding the signal sequence) [17] as previously described [16], and affinity-purified on the antigen coupled to Affigel 10/15 using previously published methods [18]. Murine anti-human GPVI monoclonal antibodies, 1G5 and 1A12, have been described elsewhere [7].…”
Section: Antibodiesmentioning
confidence: 99%
“…Third, we showed that a patient with an anti-GPVI autoantibody associated with autoimmune idiopathic thrombocytopenic purpura (ITP) had platelets with lower than normal levels of surface GPVI by flow cytometry, and, in contrast to normal platelets, detectable $10 kDa membrane-associated remnant fragment of GPVI western blotted by the anti-cytoplasmic tail antibody [16]. We used a newly developed enzyme-linked immunosorbent assay (ELISA) to measure soluble GPVI in this patient, and showed an $10-fold increase above normal plasma, indicating that soluble plasma GPVI may be a useful platelet-specific biomarker for ITP [16], other platelet-related autoimmune disorders, and possibly thrombotic disorders.…”
Section: Introductionmentioning
confidence: 98%
“…Surface levels of platelet receptors were measured by mixing PRP with saturating amounts of PE-labeled anti-CD41a (α IIb subunit of α IIb β 3 ), anti-GPIbα (AK2), anti-GPVI (1G5), anti-CD9, or isotype-matched control for 30 min in the dark at room temperature, and washing twice with TS/EDTA. Platelet pellets were resuspended in 0.5 ml TS/EDTA and analyzed in a FACSCalibur (Becton Dickinson, San Jose, Calif., USA) [19]. Analysis of GPVI-dependent intracellular ROS using the ROS-sensitive fluorescent dye H 2 DCF-DA was performed as previously described [5].…”
Section: Methodsmentioning
confidence: 99%